World happiness report 2013 - Helliwell, John F.; Layard, Richard; Sachs, Jeffrey (New York, N. Y. Sustainable Development Solutions Network, 2013)
The World Happiness Report reviews levels of happiness across developed and developing nations, and presents ranking tables on national and regional happiness. The first report in 2012 featured a broad examination of the data; this second report in 2013 considers more specific issues in measurement, explanation, and policy.
Introduction - - World Happiness: Trends, Explanations and Distribution - - Mental Illness and Unhappiness - - The Objective Benefits of Subjective Well-Being - - Restoring Virtue Ethics in the Quest for Happiness - - Using Well-Being as a Guide to Policy - - The OECD Approach to Measuring Subjective Well-Being - - From Capabilities to Contentment: Testing the Links Between Human Development and Life Satisfaction
Keywords: Happiness -- Economic aspects -- Statistics; Happiness -- Social aspects -- Statistics; Happiness -- Measurement; Quality of life -- Measurement; Well-being -- Measurement